2014 ESC/EACTS GUIDELINES ON MYOCARDIAL REVASCULARIZATION - Stephan Windecker; Philippe Kolh; Fernando Alfonso; Jean-Philippe Collet; Jochen Cremer; Volkmar Falk; Gerasimos Filippatos; Christian Hamm; Stuart J. Head; Peter Jüni; A. Pieter Kappetein; Adnan Kastrati; et al. (Российский кардиологический журнал, 2015)
.